Synthesisation of formic acid modulated aluminium based metal-organic frameworks (MOFs) for cooling and dehumidification - Medya, Saikat (Nanyang Technological University, 2020)
Referring to the present scenario of the climatic condition of the globe, inhibiting the amount of consumption of energy is always of great importance in combatting the grave situation of enhanced global warming. Adsorption-assisted heat pumps and chillers can predominantly help us in achieving the same. Due to some striking property, Metal-Organic Frameworks have been identified as the potential substitute for a solid adsorbent in recent years that can be applied in AHP (adsorption heat pump) and ADC (adsorption cooling). This report depicts the synthesisation of formic acid modulated (fam) Aluminium Fumarate followed by its surface characterisation. The parent Al Fumarate is modulated with 7.5ml, 15ml and 22.5ml of formic acid to improve the thermal stability and water adsorption capability in terms of uptake and kinetics. Employing the TEM and PXRD techniques, the characteristics of newly generated fam Al Fumarate are presented. A significant reduction in the synthesis time is observed due to the elongation of Al Fumarate particles by the addition of formic acid in different concentrations. In order to evaluate their porous properties, nitrogen adsorption is performed. Later, for water-adsorption characterization, a gravimetric analyser is employed to measure the water uptakes and kinetics at various temperatures and pressures up to the conditions of saturation. The best performance is depicted by the aluminium fumarate mixed with 15 ml formic acid. The difference between uptake and offtake of water vapour is found to be 7.4% higher than the parent aluminium fumarate. The kinetics are also found higher. Thus, the fam-based Al Fumarate metal-organic frameworks (MOFs) are considered as promising adsorbents for low temperature driven as well as adsorption assisted heat transformation applications.